Storytelling in the moment : exploring a contemporary verbal art in Britain and Ireland - Howes, Michael, ....- (Gent : Academia Press, 2014)
It comes as a surprise to many that the elemental human impulse to tell stories, far from being the exclusive realm of children's bedtime, long-forgotten civilisations and remote cultures, is also a burgeoning creative art form here, now, in twenty-first century, postindustrial societies. Storytelling in the Moment is a wide-ranging, multidisciplinary yet accessible exploration of contemporary verbal storytelling in Britain and Ireland. Primary research focuses attention on the working practices of today's storytellers, the role of the listener/participant in a storytelling event, the informal groups and established organisations that sustain its development, the multifaceted roles that storytelling now plays in our society and the complex network interconnections that link its component parts. It also seeks to reveal how an emergent, grassroots, socio-cultural movement can become ubiquitous in society but pass largely unnoticed by a wider public in an age of global mass-media. The sometimes unconventional research methodologies, narrative forms and conversational style of this study owes much to the author's extended careers as filmmaker of music, arts, humanities and public service documentaries and as screenmedia consultant to UK and worldwide governments and international agencies.
Keywords: Communicatie -- Vertellen; Go international; International office; Media -- Communicatie